2008
DOI: 10.1016/j.colsurfa.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of colloidal gas aphrons (microfoams)

Abstract: This paper reports on the effect of surfactant concentration and pipe shape and size on the rheological properties of colloidal gas aphrons (CGA) or microfoams. CGA consists of closely packed spherical gas bubbles with diameter ranging from 10 to 100 microns surrounded by a surfactant shell. It is produced by stirring an aqueous surfactant solution at high speed in a baffled beaker. Pipe flow experiments were performed in cylindrical pipes with diameter ranging from 1.0 to 3.0 mm under adiabatic laminar flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…The hypothesized structure of a microbubble comprises of a gas core encapsulated by multiple layers of surfactant molecules, which retard coalescence of the microbubbles, thereby giving it remarkable stability compared to conventional bubbles [4]. This feature coupled with a large interfacial area arising from the small bubble size has resulted in its applications in separation processes [5][6][7][8][9]. It has been suggested that microbubble dispersions can enhance bioremediation by effectively increasing mass transfer of oxygen and nutrients in the subsurface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesized structure of a microbubble comprises of a gas core encapsulated by multiple layers of surfactant molecules, which retard coalescence of the microbubbles, thereby giving it remarkable stability compared to conventional bubbles [4]. This feature coupled with a large interfacial area arising from the small bubble size has resulted in its applications in separation processes [5][6][7][8][9]. It has been suggested that microbubble dispersions can enhance bioremediation by effectively increasing mass transfer of oxygen and nutrients in the subsurface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the effects of surfactants on dynamic phenomena in foams were studied by several other research groups. 25,[47][48][49][50] In the current review we summarise the progress achieved so far in these studies. Comparison with the results of the various research groups is made, and some open questions, deserving further investigation, are discussed.…”
Section: -1432mentioning
confidence: 99%
“…The constant n is called flow index and gives a measure of degree of departure from Newtonian behaviour. The parameter n and K are independent of shape of the column [26]. The value of n and K is calculated experimentally in a horizontal pipe from the wall shear stress (t) and the apparent shear rate (g a ).…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The parameter K 0 and the flow consistency index (K) of the microbubble suspension are related as [26] …”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%